Role of transversal concentration gradient in detonation propagation. (22nd February 2019) - Han, Wenhu; Wang, Cheng; Law, Chung K.
Abstract : The role of a transversal concentration gradient in detonation propagation in a two-dimensional channel filled with an $\text{H}_{2}{-}\text{O}_{2}$ mixture is examined by high-resolution simulation. Results show that, compared to propagation in homogeneous media, a concentration gradient reduces the average detonation velocity because of the delay in reaching downstream reaction equilibrium, leading to a large amount of unreacted $\text{H}_{2}$ and hence significant species fluctuations. The transversal concentration gradient also enhances the cellular detonation instability. Steepening it reduces considerably the number of triple points on the front, lengthens the global detonation front structure on average and consequently increases the deficit of the average detonation velocity. It is further found that the interaction of the leading shock with the transversal concentration gradient influences the formation of local $\text{H}_{2}$ bump and thus the unreacted pocket behind the front, while the transverse wave causes mixing and burning of the residue fuel downstream. Nevertheless, for the steepened concentration gradient, a transverse detonation is present and consumes the fuel in the compressed and preheated zone by the leading shock; consequently, the detonation velocity deficit is not increased significantly for detonation with the single-head propagation mode close to the limit.